Potensi Ekstrak Oligosakarida Ubi Jalar Sebagai Prebiotik Bakteri Probiotik Akuakultur (The Potential of Sweet Potato Oligosaccharide Extract as Aquaculture Probiotic Bacteria Prebiotic) - Wida Lesmanawati; Widanarni Widanarni; Sukenda Sukenda; Wahyu Purbiantoro (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2013)
Sweet potato contains non digestible oligosaccharides that functions as prebiotics. The processing will affect the chemical composition of sweet potato. This study aimed to find the best preparation method of sweet potato (Ipomoea batatas) that can produce the highest oligosaccharide extract and test the prebiotic potential of the extract to support the growth of bacteria SKT-b which has been shown to act as a probiotic for shrimp. Trial I: test the preparation method of sweet potato to obtain the best oligosaccharides extract. The treatment consisted of three different preparation methods, raw potato flour, raw potato flour steamed, and steamed potato flour. Oligosaccharides from potato flour of each preparation method was then extracted and analyzed using High Performance Liquid Chromatography. Potato oligosaccharides extract from best preparation method, was dried in freeze dryer and used for later experiments. Trial II: test the potato oligosaccharides extract as prebiotic in supporting the growth of probiotic bacteria SKT-b (in vitro). This experiment was conducted to determine the combinations of prebiotic dose with inoculants concentrations that result the best growth of bacteria SKT-b. Liquid culture bacteria SKT-b concentrations of 107, 108, 109, and 1010 cfu ml-1 were cultured in sterile sea water mixed with prebiotics concentrations of 0, 1, 2 and 3% v/v. The extract of steamed potato flour contains the highest oligosaccharides, and may act as prebiotics to support the growth of probiotic bacteria SKT-b. Prebiotics 3% and probiotics SKT-b 1010 cfu ml-1 was the best sinbiotic combination, which showed the highest growth of probiotic bacteria.Keywords: oligosaccharides, probiotics SKT-b, sinbiotic, sweet potato